Pengaruh Variabel Fundamental dan Makroekonomi pada Struktur Modal dan Nilai Perusahaan (Studi pada Perusahaan Property dan Real Estate di BEI ) - Moeljadi Moeljadi; Kusuma Ratnawati; Afriani Afriani (Akutansi Bisnis & Manajemen ( ABM ), 2015)
this study aims to examine and analyze the influence of fundamental variables consisting of profitability, firm size, firm growth, and asset structure and macroeconomic variables consisting of interest rate, inflation and the exchangerate on the capital structure and corporate value. The Study population was 26 property and real estate companies listed on the Indonesia Stock Exchange during 2008-2013. The data collection were using census and the data analysis methods used path analysis. the result showed that profitability and growth of the company have the negative effect on the capital structure,However, the influance of interest rate, inflation and exchange rate showed not significantly. In relation with the company's value, profitability and firm size has positive effect while the structure of assets, exchange rate and capital structure negatively effect the value of the company. the interest rate and inflation proved to have no effect on firm's value.